Buried Versus Exposed Kirschner Wires Following Fixation of Hand Fractures: l Clinician and Patient Surveys. Issue 4 (April 2018) - Gardiner, Matthew D.; Gardiner, Sonya; Issa, Fadi; Jain, Abhilash; Lloyd-Hughes, Hawys; Pezas, Theodore; Rodrigues, Jeremy N.; Wormald, Justin C. R.; Acquaah, Frank; Brierley, Neil; Bickerton, Shixin; Chow, Whitney; et al.
Abstract : Background: Fractures of the metacarpals and phalanges are common. Placement of Kirschner wires (K-wires) is the most common form of surgical fixation. After placement, a key decision is whether to bury the end of a K-wire or leave it protruding from the skin (exposed). A recent systematic review found no evidence to support either approach. The aim of study was to investigate current clinical practice, understand the key factors influencing clinician decision-making, and explore patient preferences to inform the design of a randomized clinical trial. Methods: The steering group developed surveys for hand surgeons, hand therapists, and patients. Following piloting, they were distributed across the United Kingdom hand surgery units using the Reconstructive Surgery Trials Network. Results: A total of 423 hand surgeons, 187 hand therapists, and 187 patients completed the surveys. Plastic surgeons and junior surgical trainees preferred to leave K-wires not buried. Ease of removal correlated with a decision to leave wires exposed, whereas perceived risk of infection correlated with burying wires. Cost did not affect the decision. Hand therapists were primarily concerned about infection and patient-related outcomes. Patients were most concerned about wire-related problems and pain. Conclusion: This national survey provides a new understanding of the use of K-wires to manage hand fractures in the United Kingdom. A number of nonevidence-based factors seem to influence the decision to bury or leave K-wires exposed. The choice has important clinical and health economic implications that justify a randomized controlled trial.